2014
DOI: 10.1016/s1470-2045(14)70119-6
|View full text |Cite
|
Sign up to set email alerts
|

Statins and breast cancer prognosis: evidence and opportunities

Abstract: SUMMARY Much preclinical and epidemiologic evidence supports anticancer effects of HMG-CoA reductase inhibitors (statins). Epidemiologic evidence does not support an association between statin use and reduced breast cancer incidence, but does support a protective effect of statins—particularly simvastatin—on breast cancer prognosis. We argue that the current evidence base is sufficient to justify a clinical trial of breast cancer adjuvant therapy with statins. We advocate for such a trial to be initiated witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 77 publications
(100 reference statements)
7
141
4
1
Order By: Relevance
“…Furthermore, this benefit was confined to patients who used lipophilic statins and did not extend to users of hydrophilic statins. This strengthens the hypothesis derived from preclinical studies that the anti-cancer effect of statins may be independent of its cholesterol lowering effect and mediated by modulation of cell signaling (Ahern et al 2014;Manthravadi et al 2016). There is also a paucity of data pertaining to the role of statins across a spectrum of breast cancer molecular subtypes.…”
Section: Effect Of Statins In Animal and Human Studiessupporting
confidence: 72%
See 2 more Smart Citations
“…Furthermore, this benefit was confined to patients who used lipophilic statins and did not extend to users of hydrophilic statins. This strengthens the hypothesis derived from preclinical studies that the anti-cancer effect of statins may be independent of its cholesterol lowering effect and mediated by modulation of cell signaling (Ahern et al 2014;Manthravadi et al 2016). There is also a paucity of data pertaining to the role of statins across a spectrum of breast cancer molecular subtypes.…”
Section: Effect Of Statins In Animal and Human Studiessupporting
confidence: 72%
“…Ahern et al (2014) suggested that statins, particularly simvastatin, may reduce the risk of breast cancer recurrence. Murakami et al (2016) demonstrated that lovastatin is a potential chemopreventive agent against breast cancer.…”
Section: Effect Of Statins In Animal and Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been hypothesised that the potential anti-cancer effect of statins is restricted to lipophilic statins. (Ahern et al, 2014) Also, the serum statin concentrations achieved with cardiovascular protective doses of the medication (e.g. simvastatin 40mg) may not be sufficient to induce the anti-cancer effects observed in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…9 In accordance with this result, a recent report showed that the recurrence rates of breast cancer can be reduced by statins. 10 Other types of cancers, such as lung adenocarcinomas and head and neck squamous cell carcinomas, also overexpress the ARF6-based pathway (see refs. 4, 7).…”
mentioning
confidence: 99%